Comparing Nursing Student Competence in CPR before and after a Pedagogical Intervention. (21st February 2020) - Roel, Siv; Bjørk, Ida Torunn
Abstract : Nursing students must be able to initiate and perform effective cardiopulmonary resuscitation (CPR) when they start their career in nursing. Studies show that students' competency in CPR is deficient, indicating that better training is necessary during nursing education. This study reports on the differences in nursing students' competence in CPR before and after a longitudinal pedagogical intervention across the curriculum. Changes in the curriculum were relocation and added testing of CPR skills, inclusion of a course in defibrillation, a knowledge test as stimuli before simulation, and more simulation practice with deteriorating patients. This was a comparative study between two cohorts of students in the bachelor in nursing education. We measured knowledge and compression performance in the students' final year of education. Students in cohort 2, who received the pedagogical intervention, had a significant higher total knowledge score than students in cohort 1. Students' mean depth and number of correct compressions was similar. Students in cohort 2 had a significantly higher mean rate of compressions, number of compressions per minute, and mean number of compressions with incorrect hand positions. Although the new curriculum afforded more hands-on practice of CPR, it was not enough to improve the students' performance to match the demands set out in national and international guidelines.